ANALISIS PENGARUH JENIS PLASTIK TERHADAP DENSITAS DAN KUAT TEKAN PADA BATAKO RINGAN BERBAHAN LIMBAH PLASTIK DAN BATU APUNG - Sopyan Ali Rohman; Muhammad Ibadurrahman; Dedy Dharmawansyah (Hexagon Jurnal Teknik dan Sains, 2020)
The amount of plastic used in this era has many impacts, one of which is plastic waste, but this shows that plastic has many benefits and advantages so that it is used in almost all things in everyday life. Reuse (recycling) of plastic will be very helpful in dealing with plastic waste problems. One alternative to plastic recycling is the use of plastic waste as a material for making lightweight bricks. Problems that are often encountered in the use of conventional brick in this era are the density (density) and compressive strength, where the expected results are with a low density (density), can produce high compressive strength. Presentation of the above problems makes the writer interested in researching the use of plastic waste to be used as raw material for making lightweight bricks. In this study used 4 variations of plastic types, namely PP, LDPE, and HDPE, making plastic specimens mixed with pumice waste because it has porous and lightweight characteristics, with a ratio of 50:50 from volume. With each variation consists of 2 (two) beam-shaped samples to be tested for density (?) and compressive strength (P). A total of 6 samples. The results showed that LDPE plastic material mixed with pumice has the best density and compressive strength compared to other types of mixtures with the value of ? = 0.76g / cm2, and P = 123.15kg / cm2 or 12.08MPa.